1998
DOI: 10.1074/jbc.273.20.12669
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Arginines by 2,3-Butanedione and Phenylglyoxal Causes Closure of the Mitochondrial Permeability Transition Pore

Abstract: We have investigated the role of arginine residues in the regulation of the mitochondrial permeability transition pore, a cyclosporin A-sensitive inner membrane channel. Isolated rat liver mitochondria were treated with the arginine-specific chemical reagent 2,3-butanedione or phenylglyoxal, followed by removal of excess free reagent. After this treatment, mitochondria accumulated Ca 2؉ normally, but did not undergo permeability transition following depolarization, a condition that normally triggers opening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 38 publications
4
43
0
Order By: Relevance
“…It has been reported that the mitochondrial permeability transition pore can be regulated by the oxidation of sulfhydryl groups and membrane surface potential (61) and following ⌬⌿ m depolarization, would likely favor the formation of a disulfide bridge with C-R(7) within the pore, as supported by studies showing that dithiol, through dithiol-disulfide interconversions, control the pore conformation of the mPTP (62). The anchoring of the positively charged C-R(7) peptide within the channel could then interfere with the otherwise massive calcium entry into the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that the mitochondrial permeability transition pore can be regulated by the oxidation of sulfhydryl groups and membrane surface potential (61) and following ⌬⌿ m depolarization, would likely favor the formation of a disulfide bridge with C-R(7) within the pore, as supported by studies showing that dithiol, through dithiol-disulfide interconversions, control the pore conformation of the mPTP (62). The anchoring of the positively charged C-R(7) peptide within the channel could then interfere with the otherwise massive calcium entry into the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 82%
“…The mechanism for voltage sensing by voltage-dependent ion channels is based on the movement and reorientation of positively charged amino acids in the transmembrane electric field (27). Based on (i) the effect of arginine modification on PTP conformation and (ii) the exquisite sensitivity of PTP opening and closing to small structural differences between the arginine-reactive compounds, we have proposed that the arginine(s) is located on a putative voltage-sensing element of the PTP (19,20). Covalent modification of the voltage-sensing arginines is expected to exert a large influence on sensor orientation and therefore on pore conformation.…”
mentioning
confidence: 99%
“…5), an apoptogenic kinase inhibitor and inducer of mitochondrial depolarization, swelling, outer membrane rupture, and cytochrome c release (Scarlett et al, 2000;Tafani et al, 2001;Duan et al, 2003). Previous work has demonstrated that RCS, including MG, glyoxal, and the synthetic cell-permeable MG analog PG, block MPT pore opening, transmembrane potential dissipation, and mitochondrial swelling induced by high Ca 2ϩ and ganglioside GD3, known inducers of mitochondrial pathways of apoptosis by MPT pore opening (Eriksson et al, 1998;Johans et al, 2005). Consistent with involvement of MPT pore opening in carbonyl scavenger induction of melanoma cell apoptosis, cyclosporine A treatment suppressed DMC-induced apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%